Pupil participation and playground design: listening and responding to children's views. Issue 4 (2nd October 2017) - Pearson, Rebecca; Howe, Julia
Abstract: This article outlines a small-scale research project that attempted to involve primary aged pupils actively in the redesign of their school playground. The project stemmed from concerns raised by school staff regarding the frequency of problematic behaviours during unstructured times, particularly lunchtimes, and the decision to redesign the playground was one component of a larger scale research project. This article provides a critical account of this process, and an overview of the approach taken to involve children as co-researchers to ensure that their views were not only heard, but that they played a key role in decisions that would affect them. This offers an alternative way in which educational psychologists (EPs) can address teacher concerns regarding behaviour by attempting to involve and empower young people in the process.